PEMANFAATAN SERBUK CANGKANG KERANG SIMPINGSEBAGAI SUBSITUSI PASIR - Aziz, Muhamad Rifqi; Abdilla, Raihan; Rickianto, Rio; Yoladissa, Naviera; Herlina, Liana; Mahendra, Andhika; Aziz, Rifqi (Universitas Trisakti, 2024)
The increase in the demand for concrete materials has triggered the mining of stone, which is a constituent material of concrete as sand, resulting in a decrease in the amount of natural resources available for concrete construction purposes. The composition of concrete consists of fine aggregate, coarse aggregate, cement, water, and additives. The use of scallop shell powder as a sand substitute encourages the utilization of local materials, and shows concern for the environment. This study aims to determine the comparison of the compressive strength value of normal concrete with the compressive strength value of concrete using scallop shell powder by 2.5%, 5%, 7.5% and 10% of the number of test specimens as many as 20 samples.The method used in this research uses experimental methods in the laboratory. The specimens used werecylinders with a diameter of 15 cm and a height of 30 cm. The planned concrete quality is f'c = 30 Mpa.The compressive strength of normal concrete is 16.7 MPa at the age of 28 days and the compressivestrength of shell concrete with a composition of 2.5%, 5%, 7.5%, and 10 produces a compressive strengthof 11.6 MPa; 14.7 MPa; 13.72 MPa, and 12.45 MPa at the age of 28 days. The results of the study indicate that the lower the proportion of shell powder, the higher the compressive strength value, but it cannot exceed the compressive strength value of normal concrete.